The complement system and its involvement in inhibition of Batrachochytriym dendrobatidis, a lethal fungal pathogen of amphibians - Helen R. Pacheco; Jennifer Rodriguez Reynoso; Megha M. Tenneti; Keely M. Rodriguez; Jamie Voyles (Frontiers in Amphibian and Reptile Science, 2024)
The field of ecological immunology, or ecoimmunology, has provided valuable insights on the immune responses of diverse host organisms threatened by infectious diseases in many different environments. One infectious disease that has been particularly notable for its impacts on host populations is amphibian chytridiomycosis, which has been linked with amphibian declines around the world. Amphibian immune responses to the pathogen that causes chytridiomycosis (Batrachochytriym dendrobatidis) are not well understood but thought to involve innate immune factors, including the complement system. In this study, we tested the ability of complement proteins to inhibit B. dendrobatidis in in vitro challenge assays. We found that complement proteins from amphibian plasma that were not heat inactivated reduced the viability and growth of B. dendrobatidis. The inhibitory efficacy was similar to effects on Pseudomonas fluorescens, a bacterium that is known to be inhibited by complement protein activation. These findings suggest inhibition of B. dendrobatidis that is consistent with the involvement of the complement system. In addition, we provide methods for standardizing pathogen killing assays, and set a foundation for further investigations on the amphibian complement system and other immune responses to amphibian chytridiomycosis.